Efficacy and safety of adding gemtuzumab ozogamicin to conventional chemotherapy for adult acute myeloid leukemia: a systematic review and meta-analysis. Issue 1 (1st January 2022) - Guo, Yuancheng; Deng, Lijuan; Qiao, Yanhong; Liu, Bei
ABSTRACT: Introduction: Compared with the 3 + 7 regimen, the addition of gemtuzumab ozogamicin (GO) has improved survival in patients with acute myeloid leukemia (AML). We conducted a systematic review and meta-analysis to examine the overall efficacy and safety of GO in combination with conventional chemotherapy regimens in patients with AML. Methods: We searched several databases (MEDLINE, Embase, Web of Science and Cochrane Library). Hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated for overall survival (OS) and relapse-free survival (RFS); odds ratios (ORs) with 95% CIs were calculated for the other outcomes. Results: Ten records involving 11 randomized controlled trials (RCTs) met the inclusion criteria. GO plus induction chemotherapy significantly increased RFS (HR: 0.84, 95% CI: 0.73–0.98), decreased the incidence of relapse (OR: 0.78, 95% CI: 0.68–0.91) and resistant disease (OR: 0.72, 95% CI: 0.61–0.84), and had no significant effect on the rate of complete remission (CR) with or without incomplete platelet recovery (OR: 1.21, 95% CI: 0.94–1.55), 30-day mortality (OR: 1.25, 95% CI: 0.99–1.57). Subgroup analysis showed significant OS benefits for patients with favorable cytogenetic (HR: 0.50, 95% CI: 0.28–0.89) or given GO at induction stage (HR: 0.91, 95% CI: 0.84–1.00). Compared with other dosing schedule groups, 3 mg/m 2 fractionated schedule had a greater RFS benefit (HR: 0.52, 95% CI: 0.36–0.76) and lower relapse risk (OR: 0.48, 95% CI: 0.28–0.84). Conclusions: Adding low-dose GO to induction or both induction and post-remission chemotherapy has considerable efficacy and unequivocal safety for newly diagnosed adult AML.